2012
DOI: 10.3892/ol.2012.810
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogenesis-related microRNAs in hepatocellular carcinoma by expression profiling

Abstract: Abstract. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors of the liver. Since postoperative recurrence and intrahepatic metastases occur frequently, the postoperative 5-year survival rate is low. To investigate the molecular mechanisms of HCC progression, mRNA as well as microRNA (miRNA) expression levels have been profiled in various studies. However, no previous study has comprehensively compared the expression of miRNAs in HCC patients with various clinical features using the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 57 publications
(39 reference statements)
4
46
1
1
Order By: Relevance
“…It is upregulated in breast cancer (24) and early cerebral aneurysm (12), and downregulated in hepatocellular carcinoma (25) . It has also been reported that miR-448 is the most downregulated microRNA following chemotherapy in breast cancer (13), suggesting that it may act as an oncogene or anti-oncogene in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is upregulated in breast cancer (24) and early cerebral aneurysm (12), and downregulated in hepatocellular carcinoma (25) . It has also been reported that miR-448 is the most downregulated microRNA following chemotherapy in breast cancer (13), suggesting that it may act as an oncogene or anti-oncogene in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the level of VCP and miR-129-5p in HCC samples was significantly distinctive from that in adjacent normal tissues, the two molecules may be novel indicators for prediction of the genesis of HCC. Katayama et al referred miR-129 as a novel candidate for HCC biomarkers regardless of virus infection [92]. Additionally, a negative correlation between miR-129-5p expression levels and ETS1 levels was reported in HCC tissues, suggesting that miR-129-5p could be a helpful prognostic marker and/or therapeutic target in HCC [77].…”
Section: Mir-129 As a Biomarker For Cancer Diagnosis And Prognosismentioning
confidence: 99%
“…Since miRNAs perform important roles in various pivotal biological processes, dysregulated miRNA expression has been implicated in a variety of human diseases, including chronic HBV infection and hepatocarcinogenesis (19). An increasing amount of evidence has indicated that dysregulation of miRNAs has important roles in HBV infection and HBV-associated HCC (9,(20)(21)(22). Numerous studies have demonstrated that the HBx protein is associated with the regulation of miRNAs, which affects basic tumor processes, including cellular proliferation, differentiation and metastasis (12,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%